Mufangji Decoction and Its Active Ingredient Patchouli Alcohol Inhibit Tumor Growth through Regulating Akt/mTOR-Mediated Autophagy in Nonsmall-Cell Lung Cancer - Liu Yang (Hindawi Limited, 2021)
Background. Nonsmall-cell lung cancer (NSCLC) is the main type of lung cancer, whose morbidity and mortality rank first among malignant tumors. More than 70% of NSCLC patients are diagnosed at locally advanced or advanced stage, missing the best operation period. Chemotherapy and targeted therapy are important means for the treatment of advanced NSCLC, but various side effects seriously affect the curative effect and the life quality of NSCLC patients. Our previous clinical practice has shown that Mufangji Decoction, a classic traditional Chinese medicine, has a significant curative effect in the treatment of NSCLC, but the specific mechanism is not clear. This study intends to explore the potential mechanism of Mufangji Decoction and its active ingredient patchouli alcohol against NSCLC and to provide a scientific basis for the prevention and treatment of NSCLC by traditional Chinese medicine. Methods. The in vivo and in vitro experiments were performed to evaluate the antitumor effects and investigate the underlying mechanism of Mufangji Decoction and its active ingredient patchouli alcohol. Network pharmacology was applied to analyze the effective ingredients and potential targets or signaling pathways of Mufangji Decoction. Results. Our current study shows that Mufangji Decoction can effectively inhibit the growth of subcutaneous transplantation of NSCLC. The following network pharmacological analysis and in vivo experiment suggest that patchouli alcohol is one of the main active ingredients of Mufangji Decoction and exerts antitumor effects. Further mechanism investigation reveals that the antitumor effect of patchouli alcohol is related to the induction of Akt/mTOR signaling pathway-mediated autophagy in NSCLC cells. Conclusion. Mufangji Decoction and its active ingredient patchouli alcohol might exert their antitumor effects in NSCLC partly through regulating Akt/mTOR-mediated autophagy, providing the evidence that traditional Chinese medicine might be a key approach for NSCLC treatment via targeting the Akt/mTOR signal axis.